Negotiating Self-Expression, Digital Privacy, and Religious Identity on Instagram’s Close Friends: A Qualitative Study of Mosque Youth - Ummu Zainab Napitupulu; Muhammad Husni Ritonga (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2026)
This study examines how mosque youth use Instagram’s Close Friends feature to negotiate self-expression, digital privacy, and religious identity. A descriptive qualitative approach was employed with eight members of the Nurul Hidayah Mosque Youth Organization in Pertahanan Village, aged 17–20 years. Participants were selected purposively because they were active Instagram users who used Close Friends to share personal content. Data were collected through semi-structured in-depth interviews conducted in April 2026, one month of non-participant digital observation of relevant Close Friends stories, and consented documentation. The data were analyzed through data reduction, data display, and conclusion drawing, supported by source and method triangulation and member checking. Close Friends functioned as a semi-private communication space in which participants shared personal opinions, relationship-related experiences, academic pressures, emotional conditions, religious reflections, social criticism, and everyday activities with selected audiences. Participants managed disclosure by choosing trusted audiences, filtering sensitive content, and using indirect forms of expression such as music, quotations, emojis, and short texts. The feature was used to maintain interaction with close friends, seek emotional relief, express opinions, share entertainment, and communicate more comfortably than through public accounts. Religious identity was one consideration when participants assessed possible social judgment and the image they wished to maintain, alongside personal needs, friendship relations, and anticipated audience responses. Restricted audiences, however, did not fully prevent misunderstanding, interpersonal tension, screen capture, or the redistribution of content. Close Friends functioned as a negotiated communication space in which personal expression, social relationships, reputational concerns, and religious identity shaped participants’ privacy practices.